Ischemic optic neuropathy and high-level anticardiolipin antibodies in primary Sjogren's syndrome (1995)
A 39-year-old woman with recurrent severe anterior ischemic optic neuropathy in the setting of Sjögren's syndrome was found to have high-titer IgM anticardiolipin antibodies (aCL) that were enhanced by the phospholipid-binding glycoprotein ?2GP1. The recognition of IgM aCL-associated vasculopathy as a possible etiologic factor in the optic neuropathy in Sjögren's syndrome may be relevant in deciding appropriate therapy.